Composition and structure of plankton communities in the Bering Sea - K. M. Gorbatenko (Известия ТИНРО, 2021)
On the data of long-term surveys, mean biomass of plankton in the epipelagic layer of the Bering Sea is evaluated as 821.3 mg/m3 (1058.2 mg/m3 in shelf areas and 760.6 mg/m3 in the deep-water areas) and the stock as 245.1•106 t WW (64.4 • 106 t over the shelf and 180.7 • 106 t in the deep-water sea). By taxa, the average annual portions are: 55.1 % for copepods, 26.3 % for arrowworms, 10.8 % for euphausiids, 3.2 % for medusas, and 2.9 % for amphipods. The dominant species are the arrowworm Sagitta elegans (26.3 %) and the copepod Eucalanus bungii (19.7 %); other mass species are: large-sized copepods Neocalanus cristatus (10.4 %), Neocalanus plumchrus + Neocalanus flemingeri (7.8 %) and Calanus glacialis + Calanus marshallae (5.1 %), euphausiids Thysanoessa raschii (3.5 %) and Thysanoessa longipes (3.4 %), small-sized copepods Metridia pacifica (3.5 %) and Oithona similis (3.5 %), medusa Aglantha digitale (3.2 %).